Synthesis of silver nanoparticles by using tea leaf extract from Camellia Sinensis - Loo YY (Dove Medical Press, 2012)
Yuet Ying Loo,1 Buong Woei Chieng,2 Mitsuaki Nishibuchi,3 Son Radu11Centre of Excellent for Food Safety Research, Faculty of Food Science and Technology, Universiti Putra Malaysia, Selangor, Malaysia; 2Department of Chemistry, Faculty of Science, Universiti Putra Malaysia, Selangor, Malaysia; 3Center for South East Asian Studies, Kyoto University, Kyoto, JapanAbstract: The development of the biological synthesis of nanoparticles using microorganisms or plant extracts plays an important role in the field of nanotechnology as it is environmentally friendly and does not involve any harmful chemicals. In this study, the synthesis of silver nanoparticles using the leaves extract of Chinese tea from Camellia sinensis is reported. The synthesized nanoparticles were characterized using UV-vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) spectroscopy. The XRD analysis shows that the synthesized silver nanoparticles are of face-centered cubic structure. Well-dispersed silver nanoparticles with an approximate size of 4 nm were observed in the TEM image. The application of the green synthesized nanoparticles can be used in many fields such as cosmetics, foods, and medicine.Keywords: silver, nanoparticles, green synthesis, leaf extract, transmission electron microscopy, nanotechnology